1990
DOI: 10.1128/jvi.64.8.3844-3852.1990
|View full text |Cite
|
Sign up to set email alerts
|

Preassembled capsids of type D retroviruses contain a signal sufficient for targeting specifically to the plasma membrane

Abstract: The capsids of Mason-Pfizer monkey virus (M-PMV), an immunosuppressive type D retrovirus, are preassembled in the infected cell cytoplasm and are then transported to the plasma membrane, where they are enveloped in a virus glycoprotein-containing lipid bilayer. The role of viral glycoprotein in intracellular transport of M-PMV capsids was investigated with a spontaneous mutant (5A) of M-PMV, which we show here to be defective in envelope glycoprotein biosynthesis. DNA sequence analysis of the env gene of mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 54 publications
2
36
1
Order By: Relevance
“…While the absence of Env did not result in the complete inhibition of transport that we observed at 20 °C, we did observe an approximately 7‐fold reduction in the rate of Gag maturation during the second and third hours of a pulse‐chase experiment, which is the time of maximum Gag release and maturation for wild‐type virus. This observation differs from a previous report from this laboratory by Rhee et al (13) that described apparently normal Gag polyprotein processing and viral release kinetics for a provirus expressing a truncated Env that is retained in the ER. While the basis for this discrepancy is not fully understood, in the initial report, pulse‐chase experiments were performed 72 h after calcium phosphate transfection, in contrast to 16 h following Fugene 6 transfection for the experiments described here.…”
Section: Discussioncontrasting
confidence: 99%
“…While the absence of Env did not result in the complete inhibition of transport that we observed at 20 °C, we did observe an approximately 7‐fold reduction in the rate of Gag maturation during the second and third hours of a pulse‐chase experiment, which is the time of maximum Gag release and maturation for wild‐type virus. This observation differs from a previous report from this laboratory by Rhee et al (13) that described apparently normal Gag polyprotein processing and viral release kinetics for a provirus expressing a truncated Env that is retained in the ER. While the basis for this discrepancy is not fully understood, in the initial report, pulse‐chase experiments were performed 72 h after calcium phosphate transfection, in contrast to 16 h following Fugene 6 transfection for the experiments described here.…”
Section: Discussioncontrasting
confidence: 99%
“…The cytoplasmic targeting/retention signal or CTRS sequence of the M‐PMV Gag polyprotein was previously demonstrated to be responsible for the intracytoplasmic assembly of retroviruses exhibiting B/D‐type morphogenesis (15,27). Here we show that the CTRS is responsible for dynein‐mediated targeting/retention of nascent Gag polyproteins at the centriolar region of the cell, and that assembly of immature M‐PMV capsids occurs at this location.…”
Section: Discussionmentioning
confidence: 99%
“…: 46 proteins of flaviviruses (2,24,34,63) and coronaviruses (58) have been demonstrated to form subviral lipoprotein particles. Retroviruses represent yet a third type of viral budding mechanism, and in this case the viral core protein precursor Gag is capable of self-assembling into enveloped virus-like particles (9,12,48,53,62), thereby indicating that binding of a cytoplasmic core protein into the membrane and its oligomerization into a core structure provide the driving force for retrovirus budding. Recently, it was reported that the core components of the rhabdovirus rabies virus was capable of assembling into extracellular enveloped particles in the absence of the viral spike proteins (36).…”
mentioning
confidence: 99%